2007
DOI: 10.1158/1535-7163.mct-06-0526
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin inhibits expression of hypoxia-inducible factor-1α through reducing hypoxia-inducible factor-1α stability and inhibiting its protein synthesis

Abstract: Chrysin is a natural flavonoid and has been shown recently to have anticancer effects. However, the mechanisms that chrysin inhibits cancers are not well known. In this study, we investigated the effects of chrysin on expression of hypoxia-inducible factor-1A (HIF-1A) and vascular endothelial growth factor in human prostate cancer DU145 cells. Chrysin inhibited insulin-induced expression of HIF-1A by reducing its stability. Chrysin increases ubiquitination and degradation of HIF-1A by increasing its prolyl hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 47 publications
6
110
0
Order By: Relevance
“…In a previous study, STAT3 signaling was not investigated, and the inhibitory effect of chrysin on Akt-modulated HIF-1α protein stability was shown only in the insulin-stimulated normoxic cells, but the mechanism was not tested in hypoxic cells (16). In 4T1 cells, the inhibition of hypoxia-induced VEGF expression and STAT3 activation by chrysin were observed at a concentration lower than that affecting Akt phosphorylation ( Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a previous study, STAT3 signaling was not investigated, and the inhibitory effect of chrysin on Akt-modulated HIF-1α protein stability was shown only in the insulin-stimulated normoxic cells, but the mechanism was not tested in hypoxic cells (16). In 4T1 cells, the inhibition of hypoxia-induced VEGF expression and STAT3 activation by chrysin were observed at a concentration lower than that affecting Akt phosphorylation ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Our results clearly show that chrysin, as well as a STAT3 inhibitor, could abrogate hypoxia-induced VEGF gene expression of 4T1 cells, through inhibition of STAT3 tyrosine phosphorylation, without decreasing HIF-1α protein levels. Chrysin has been shown to decrease HIF-1α protein levels in hypoxic DU145 human prostate cancer cells, thus abrogating insulin-induced HIF-1α protein stabilization in normoxic DU145 cells, via inhibition of Akt phosphorylation (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,12) In addition, chrysin inhibits angiogenesis by suppression of endothelial cell proliferation and migration in human umbilical vascular endothelial cells (HUVEC). [18][19][20][21] However, the potency of chrysin on lymphangiogenesis is not currently available. The chrysin at non-toxic concentration 25 μM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-asthmatic potential of chrysin on ovalbumin-induced bronchoalveolar hyperresponsiveness in rats (Caprifoliaceae) (Rahman Kang, 2009), Cyclanthera pedata Scrabs (Caigua) (Montoro et al, 2005), and bee propolis (Burdock, 1998), was reported to possess inhibition of IgE and Th2 cytokine (Yano et al, 2007), inhibition of cyclooxygenase (COX), inducible nitric oxide synthase (iNOS) (Liang et al, 2001;Cho et al, 2004;Hougee et al, 2005;Woo et al, 2005;Comalada et al, 2006;Harris et al, 2006), and hypoxia-inducible factor-1 expression (Fu et al, 2007).…”
Section: Research Articlementioning
confidence: 99%